1999
DOI: 10.1007/s002109900086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piracetam on pentylenetetrazol-kindling development, hippocampal potentiation phenomena and kindling-induced learning deficit

Abstract: Kindling is a generally accepted model for studying epilepsy development in the context of overexpression of processes of neuronal plasticity. In previous studies we have shown that establishment of kindling by repeated application of subconvulsive doses of pentylenetetrazol (PTZ) also led to marked changes in hippocampal excitability and an impairment in learning behaviour. With the intention of further investigating the relationship between kindling development, kindling-induced changes in excitability and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Therefore, it can be assumed that the ability of the neurones to react to a sufficient stimulus with a plastic change in excitability was continually enhanced. Moreover, as our previous results indicate, this change in reactivity was long-lasting even when PTZ application was interrupted for four weeks (Rü thrich et al, 1996(Rü thrich et al, , 1999. Such reactions were also recently described by .…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, it can be assumed that the ability of the neurones to react to a sufficient stimulus with a plastic change in excitability was continually enhanced. Moreover, as our previous results indicate, this change in reactivity was long-lasting even when PTZ application was interrupted for four weeks (Rü thrich et al, 1996(Rü thrich et al, , 1999. Such reactions were also recently described by .…”
Section: Discussionsupporting
confidence: 82%
“…However, it has been suggested that oxiracetam also modulates glutamatergic transmission and protein kinase C (PKC) (Raiteri et al, 1992;Fordyce et al, 1995), while aniracetam and piracetam potentiate AMPA receptor mediated ion conductance and metabotropic glutamate receptor activity (Gouliaev and Senning, 1994;Johansen et al, 1995;Noorbala et al, 1999;Pittaluga et al, 1999;Ruthrich et al, 1999). Therefore, the mechanism of action responsible for memory facilitation by nootropic drugs in not fully known, and may involve various neurotransmitters.…”
Section: Discussionmentioning
confidence: 95%
“…PIM belongs to pyrrolidones group most of which are known to influence cholinergic functions. [ 24 25 ] Along with rutin, flavonoids and many members of this group have varying action on cholinergic system. In this study, AChE activity was reduced by PIM as well as by rutin in brain.…”
Section: Discussionmentioning
confidence: 99%